Prevalence and risk factors for restless legs syndrome during pregnancy in a Northern Italian population. (19th May 2019) - Esposito, Giovanna; Odelli, Vanessa; Romiti, Lucrezia; Chiaffarino, Francesca; Di Martino, Mirella; Ricci, Elena; Mauri, Paola Agnese; Bulfoni, Alessandro; Parazzini, Fabio
Abstract: The objective of the present study was to investigate the frequency and the risk factors for restless legs syndrome (RLS) during pregnancy in an Italian population rarely studied, in epidemiological studies on the syndrome. A total of 648 women (median age: 35 years; interquartile range: 32–38), who delivered on randomly selected days at the obstetric department of our hospital, were identified. One hundred and thirty-two women (20.4%, 95% confidence interval (CI): 17.3–23.5) met the criteria for a diagnosis of RLS. The odds ratio (OR) of RLS was, in comparison with women aged <35 years, 1.69 (95% CI 1.14–2.51) in women aged ≥35 years. Subjective insufficient sleep (OR: 2.35, 95% CI 1.27–4.35) and difficulty in initiating sleep (OR: 1.73, 95% CI 1.15–2.63) increased the risk of RLS. This study confirms the high frequency of RLS in pregnant women. The risk of the condition was increased in women aged ≥35 years and in the women reporting sleep-wake disturbances during pregnancy. Impact statement: What is already known on this subject? Restless legs syndrome (RLS), a common neurological, sensorimotor disorder, is two/three times more frequent in pregnant women than in the general population. The prevalence of RLS during pregnancy ranges widely, showing differences among populations. What do the results of this study add? This study adds data about the frequency and the risk factors for RLS during pregnancy in a Northern Italian population, rarely considered in epidemiological studies on the syndrome. Older age and sleep-wake disturbances are the main factors associated with the condition. What are the implications of these findings for clinical practice and/or further research? Screening for RLS might be useful for pregnant women to manage the condition. Further research is needed to investigate and define the potential impact of RLS during pregnancy on foetal and maternal health.